2016
DOI: 10.1186/s12912-015-0121-7
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ perceptions of and satisfaction with the use of automated dispensing cabinets at the Heart and Cancer Centers in Qatar: a cross-sectional study

Abstract: BackgroundAutomated dispensing cabinets (ADCs) were introduced in 2010 and 2012 at the Heart Hospital (HH) and National Center for Cancer Care and Research (NCCCR), both run by Hamad Medical Corporation in Qatar. These medication distribution systems provide computer-controlled storage, dispensing, and tracking of drugs at the point of care in patient care units. The purpose of this study was to assess nurses’ perceptions of and satisfaction with the use of ADCs at HH and NCCCR.MethodsA cross-sectional study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 6 publications
1
27
0
Order By: Relevance
“…In general, the nurses were satisfied with ADCs and expressed they have made their work easier. This is consistent with the findings of Rochais et al (2014) and Zaidan et al (2016), who have investigated nursesṕ erceptions of, and satisfaction with, the use of ADCs [9,10].…”
Section: Discussionsupporting
confidence: 91%
“…In general, the nurses were satisfied with ADCs and expressed they have made their work easier. This is consistent with the findings of Rochais et al (2014) and Zaidan et al (2016), who have investigated nursesṕ erceptions of, and satisfaction with, the use of ADCs [9,10].…”
Section: Discussionsupporting
confidence: 91%
“…In addition, the dispensing of drugs prescribed as "if necessary" occurs only if there is a real need for use by the patient, including increasing safety. 3 These data show the contribution of the electronic dispensary to inventory control, both regarding consumption and return.…”
Section: Discussionmentioning
confidence: 92%
“…Automated drug delivery systems, popularly known as electronic dispensers for drugs and materials, are a promise of improved patient care, reduced medication errors, decreased costs, and a closer approximation of the pharmacist to direct patient care. [1][2][3] According to a technical opinion issued by the Health Technology Assessment Institute, electronic dispensaries can be defined as dispensing devices through an interface between the prescription and the equipment and can be classified as centralized (when located within the pharmacy service) or decentralized (if they are deployed in inpatient units). These systems allow the maintenance of decentralized stocks, however, controlled by the pharmacy staff.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the number of safe practice violations decreased from 54.8% to 29% and the number of medication errors decreased from 5.9% to 2.9% (Ching, Williams, Idemoto, & Blackmore, ). A study by Zaidan et al () found that 94% of nurses agreed that using a bar code system allowed them to perform their job more safely.…”
Section: Resultsmentioning
confidence: 99%
“…One study reported that 185 nurses (63.78%) were positive about using the system if they also felt it was easy to use and useful (Escobar-Rodriguez & Romero-Alonso, 2013). A study by Zaidan et al (2016) reported that 367 (95%) of nurses found it easy to log in to the system they used and that it provided them with access to all the drugs they needed. As a result, 91% were very satisfied or satisfied with the device.…”
Section: Using Robots For Medicationmentioning
confidence: 99%